Management : a total quality perspective - Bounds, Gregory M.; Dobbins, Gregory H.; Fowler, Oscar S. (Cincinnati, Ohio : South-Western College, 1995)
This book is divided into five parts: The field of management; Strategic management; Organizing to complete; Social and cultural processes; and Methods for control and improvement.
Keywords: Management; Management; Total quality management